2014
DOI: 10.4236/jmmce.2014.25048
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Copper Addition on the Mechanical and Wear Properties of Grey Cast Iron

Abstract: An alloy of cast iron and copper (Fe-Cu) has been developed using a stir cast process. The compositional, microstructural characterization and wear property of the developed Fe-Cu alloy were carried out with the aids of X-ray diffractometer, scanning electron microscope (SEM) and pin on Disc machine. The mechanical properties such as hardness and impact energy were investigated. Wear linear equations were generated with the aids of MATLAB linear fitting. The results revealed that the presence of copper (99% pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…It was confirmed that there was no significant difference according to the changes of the reaction temperature conditions, and it contained about 86% Fe and 3% Cu, indicating the formation of ferrous alloy contained Cu. Cast iron is widely used in multicomponent ferrous alloy in place of steel at considerable low cost and with optimum combination properties such as castability, machinability, and excellent wear resistance, and has high hardness and high inherent damping capabilities [19][20][21]. It is known that the addition of alloy elements, cooling rate and formation of graphite influence the properties of cast iron.…”
Section: Reduction Smelting For Ironmakingmentioning
confidence: 99%
See 2 more Smart Citations
“…It was confirmed that there was no significant difference according to the changes of the reaction temperature conditions, and it contained about 86% Fe and 3% Cu, indicating the formation of ferrous alloy contained Cu. Cast iron is widely used in multicomponent ferrous alloy in place of steel at considerable low cost and with optimum combination properties such as castability, machinability, and excellent wear resistance, and has high hardness and high inherent damping capabilities [19][20][21]. It is known that the addition of alloy elements, cooling rate and formation of graphite influence the properties of cast iron.…”
Section: Reduction Smelting For Ironmakingmentioning
confidence: 99%
“…It is known that the addition of alloy elements, cooling rate and formation of graphite influence the properties of cast iron. Copper leads to the graphitizing and pearlitization of cast iron, which are phase-stabilizing, which substantially affects mechanical properties such as strength, toughness and corrosion resistance [19][20][21][22][23][24]. Many researchers have studied the effect of Cu addition on the mechanical properties and structure formation of cast iron.…”
Section: Reduction Smelting For Ironmakingmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature clearly reveal that modifications to the grey cast iron occur with the addition of copper due to changes of the microstructure and mechanical properties. 10,14,16 However, up to now, there does not appear to have been any comprehensive investigation of the attainable morphology and wear resistance of commercial grey cast iron without and with different additions of copper under ranges of wear conditions. This omission motivated the authors to conduct a systematic study to examine the attainable morphology and wear resistance of commercial grey cast iron without and with the addition of different proportions of copper under a range of wear conditions using a pinon-disc instrument.…”
Section: Background: Effects Of Alloying Elements In Grey Cast Ironmentioning
confidence: 99%
“…9 Adding alloying elements or heat treatment to increase the hardness of the cast iron will in turn increase wear resistance beyond those of conventional grey cast irons. 10 As previously stated, advanced materials with superior mechanical properties are needed in a wide range of engineering application. For example, wear resistance is an essential characteristic for those materials subjected to friction.…”
Section: Introductionmentioning
confidence: 99%